Development of Indonesian Language Based on Spritual Project Based Learning Approach for Students of Grade VI of SDN 04 Rantau Utara Labuhan Batu - Afrida, Dede; Sibarani, Asni; Susanti, Dewi; Masythah, Irma; Triana, Heny; Ayu, Yusmaini; Sri Hartati (International Journal of Educational Research Excellence (IJERE), 2025)
Indonesian language skills for sixth-grade students of SDN 04 Rantau Utara Labuhanbatu by developing their Indonesian language speaking skills, but in reality, the ability to speak Indonesian is very low, especially at SDN 04 Rantau Utara, even though they have been studying for years. The researcher attempted to provide a solution by using Islamic-themed English teaching materials using teaching materials based on the spiritual Project-based Learning approach so that students are motivated and more confident in communicating using Indonesian, because the teaching materials presented are in accordance with the environment and conditions of the school, which is an Islamic environment, so that the interest of students in learning Indonesian increases and Indonesian language communication is created and what is expected by the author is achieved